CO03 | Early discharge and home treatment of low-risk pulmonary embolism: a cohort study (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aims: Pulmonary embolism (PE) is a common condition with a wide variety of clinical presentations and severities, making early mortality risk assessment essential to defining the most appropriate management strategy. Guidelines agree on the possibility of early discharge for patients who, based on clinical presentation, imaging, and laboratory data, present a low risk of complications. Despite evidence of efficacy and safety, home management is generally applied in only 7% of patients. The aim of this study is to analyse the characteristics and the management of patients with low-risk PE who received this diagnosis at the Emergency Department (ED) of Ospedale di Circolo (Varese).